A Review of the Welfare Impact on Pinnipeds of Plastic Marine Debris - Butterworth, Andy (Frontiers in Marine Science, 2016)
Uncounted, and usually unobserved, numbers of pinnipeds find themselves entangled in lost fishing gear, monofilament line, nets, rope, plastic packaging in the ocean or on the shoreline. These animals may carry debris wrapped around themselves for long periods, and often die as a result, sometimes from deep chronic wounds. The pinniped species most affected by this modern and manmade phenomenon are fur seals, monk seals, and California sea lions, and to a lesser extent grey, common and monk seals. Entanglement rates described range up to 7.9% of local populations annually, and the common entangling materials; packing bands, fragments of lost net, rope, monofilament line, fishery flashers and lures, long-line fishing gear, hooks and line, and bait hooks are discussed. Awareness of this issue is increasing, and local action is reported to have made measurable differences in entanglement rates, however, plastic material in the ocean is likely to be long lived, and will leave many entangled pinnpeds unreported and result in a hidden and potentially significant effect on wild animal welfare.